Peran Ibadah Dalam Membentuk Akhlak Seorang Muslim (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
The importance of worship in shaping the character of a Muslim is the purpose of this study. Worship is considered the main way to guide and direct a person towards a better, balanced, and moral life. This study was conducted using a qualitative approach and data collection techniques through literature research on relevant Islamic literature and sources. The data were analyzed descriptively to examine the relationship between character building and the practice of worship in the life of a Muslim. The results of the study indicate that worship that is performed correctly, sincerely, and in accordance with the requirements of Islamic law plays a significant role in shaping noble character or morals. Worship enhances the vertical relationship between humans and Allah SWT. It also influences the way we behave towards others in our daily lives. Good morals will help a person maintain harmonious relationships with others, foster mutual respect, honesty, and social responsibility, which in turn will result in a better and more civilized society.